(untitled) (International Current Pharmaceutical Journal, 2013)
Ficus exasperata has been extensively used in folk medicine for the treatment of many ailments. The aqueous extract of leaves of this herb reduced blood pressure through its cholinomimetic effect. In this study, different fractions of the crude extract of F. exasperata leaves (FEFIX) were evaluated on blood pressure. Fractionated extracts were obtained by successive use of different solvents on the total crude extract. Phytochemical analysis was performed for each fraction and increasing doses (0.25 to 40 mg / kg b.w.) were administered intravenously. The phytochemical screening showed that alkaloids and phenols were found in ethanol fraction (FE-FEFIX) and methanol fraction (FM-FEFIX). Saponins and tannins have been identified only in the aqueous fraction (FA-FEFIX). Decreases in blood pressure were 40.02 ± 3.08 mm Hg for the ethanol fraction (FE-FEFIX), 9.95 ± 2.09 mm Hg for the methanol fraction (FM-FEFIX) and 5.26 ± 1.46 mm Hg in the aqueous fraction (FA-FEFIX). Hypotension induced by ethanol fraction is found to be greater than those induced by the other two fractions. In conclusion, this study showed that the hypotensive effect of F. exasperata leaves was greater with its ethanol extract. Alkaloids and phenols present in this extract may be involved in the hypotensive effect. DOI: http://dx.doi.org/10.3329/icpj.v2i11.16534 International Current Pharmaceutical Journal, October 2013, 2(11): 193-195